Analisis Hukum Kebijakan Ekspor Pasir Laut: Interpretasi dan Implementasi SDGs di Kepulauan Riau - Br Tarigan, Nopita Sari; Shelvi Rusdiana; Ampuan Situmeang (JURNAL USM LAW REVIEW, 2026)
This study analyzes Indonesia’s marine sand export policy in the Riau Islands in relation to the achievement of Sustainable Development Goals (SDGs) 15 on Life on Land, against the backdrop of a policy shift from the export ban under the Decree of the Minister of Industry and Trade No. 117/MPP/Kep/2/2003 to the reauthorization of exports under Government Regulation No. 26 of 2023. This policy change gives rise to legal issues in the form of normative conflicts, inconsistencies in environmental protection objectives, and weaknesses in regulatory design in controlling the exploitation of natural resources. This research constitutes a normative-analytical legal study employing a statutory approach and a theoretical approach, analyzed through Hans Jonas’s Ethics of Responsibility and Mochtar Kusumaatmadja’s Development Law theory, with ecological impact data used solely as secondary supporting data to strengthen normative arguments rather than as empirical findings. The results indicate that Government Regulation No. 26 of 2023 inadequately regulates the effectiveness of sanctions, supervisory mechanisms, and public participation, thereby resulting in weak protection of terrestrial and coastal ecosystems and hindering the optimal achievement of SDGs 15. The novelty of this study lies in integrating the analysis of marine sand export policy with intergenerational responsibility ethics and the SDGs framework as a normative basis for strengthening environmental regulation.  Penelitian ini menganalisis kebijakan ekspor pasir laut Indonesia di wilayah Kepulauan Riau dalam kaitannya dengan pencapaian Sustainable Development Goals (SDGs) 15 tentang Kehidupan di Darat, dengan latar belakang perubahan kebijakan dari larangan ekspor melalui Keputusan Menteri Perindustrian dan Perdagangan Nomor 117/MPP/Kep/2/2003 menjadi kebijakan yang mengizinkannya melalui Peraturan Pemerintah Nomor 26 Tahun 2023. Perubahan tersebut menimbulkan persoalan yuridis berupa konflik norma, inkonsistensi arah perlindungan lingkungan hidup, serta kelemahan desain regulasi dalam mengendalikan pemanfaatan sumber daya alam. Penelitian ini merupakan kajian hukum normatif-analitis dengan pendekatan perundang-undangan dan pendekatan teori, yang dianalisis menggunakan teori Etika Tanggung Jawab Hans Jonas dan teori Hukum Pembangunan Mochtar Kusumaatmadja, dengan data dampak ekologis digunakan sebagai data pendukung sekunder untuk memperkuat argumentasi normatif, bukan sebagai temuan empiris. Hasil penelitian menunjukkan bahwa PP Nomor 26 Tahun 2023 belum secara memadai mengatur efektivitas sanksi, mekanisme pengawasan, dan partisipasi masyarakat, sehingga berimplikasi pada lemahnya perlindungan ekosistem darat dan pesisir serta tidak optimalnya pencapaian SDGs 15. Kebaruan penelitian ini terletak pada integrasi analisis kebijakan ekspor pasir laut dengan etika tanggung jawab antargenerasi dan kerangka SDGs sebagai dasar penguatan regulasi lingkungan hidup.
Keywords: Etika Tanggung Jawab; Kebijakan Pembangunan; Perlindungan Lingkungan